The Medicolegal Evaluation of Various Factors Effective on Blood Alcohol Level - Vural, Nevin; Sayın, Hülya (The Bulletin of Legal Medicine, 1996)
Accurate analysis of alcohol (ethanol) in antemortem and postmortem blood is very important for medicolegal purposes. Source of postmortem blood sample, collection and preservation conditions can effect blood alcohol levels. Femoral vein is the most suitable source for blood alcohol determination as the postmortem invasion of microorganisms spread takes place through arteries. Also head and neck veins can be used for postmortem blood sampling. Blood drawn from the heart is not ideal due to endogenous alcohol formation or biochemical alcohol oxidation. This study describes the preservative effect of sodium fluoride and sodium azide on blood alcohol level. Postmortem blood samples were stored at +4CC and +22°C for 28 days and alcohol levels were determined at the 0., 7 th, 14 th, 21st and 28th days. The results showed that sodium azide is more effective than sodium fluoride for the preservation of postmortem blood alcohol at +4°C. Key words: Blood Ethanol Analysis, Chemical Stabilisation, Endogenous Ethanol, Ethly Alcohol, Microdiffusion Analysis, Postmortem Blood Alcohol Loss, Storage Conditions.